Enhancing Human Resource Competencies Through Digital Marketing Training for MSMEs in Majasari, Pandeglang - Urika, Urika; Novian, Lona (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The aim of this study is to evaluate the level of understanding of digital marketing concepts and practices, identify challenges and obstacles in implementing digital marketing, assess the effectiveness of digital marketing training in enhancing human resource knowledge and skills, and evaluate the impact of digital marketing training on business performance and strategies to optimize its use. This research employs a mixed-method approach. The subjects of the study are micro, small, and medium enterprises (MSMEs) in Majasari District, Pandeglang Regency, with a sample size of 38 individuals. The findings indicate an improvement in the understanding of digital marketing concepts and practices among MSME operators after undergoing training. Challenges encountered include limitations in smartphone ownership, regional accessibility, packaging knowledge, and online selling experience. Digital marketing training has proven effective in enhancing the knowledge and skills of MSME human resources through strategies such as increasing training frequency, providing hands-on practice in creating social media and marketplaces for digital product marketing, and developing product logos for branding to compete in the online sales market